The implication of gut microbiota in recovery from gastrointestinal surgery - Zheng, Zhipeng; Hu, Yingnan; Tang, Jingyi; Xu, Wenjun; Zhu, Weihan; Zhang, Wei (Frontiers in Cellular and Infection Microbiology, 2023)
Recovery from gastrointestinal (GI) surgery is often interrupted by the unpredictable occurrence of postoperative complications, including infections, anastomotic leak, GI dysmotility, malabsorption, cancer development, and cancer recurrence, in which the implication of gut microbiota is beginning to emerge. The baseline of gut microbiota before surgery depends on the underlying diseases. Both preoperative procedures and GI surgery lead to a profound alteration of the composition and function of gut microbiota. The current approaches to preparing the GI tract before surgery, including fasting, mechanical bowel cleaning, and antibiotic intervention, disrupt gut microbial contribution to immune function and recovery from injury. The GI surgery involves the removal of GI segments, subsequent reconstruction of the GI tract, and destruction of the epithelial barrier, which is known to disrupt gut microbiota. In turn, the altered gut microbiota might contribute to the occurrence of postoperative complications. In addition, postoperative restoration of the gut microbiota population is still not fully understood. Therefore, we overview the current knowledge to investigate gut microbiota in the context of recovery from GI surgery, focusing on how the interaction between gut microbiota and host affects the pathogenesis of postoperative complications. A better understanding of the postoperative response of the GI tract to the altered gut microbiota may provide cues to preserve the beneficial functions and suppress the adverse effects of gut microbiota, which will help to improve the safety of GI surgery and reduce the risk of postoperative complications. Thus, targeted modulation of gut microbiota may enhance recovery from GI surgery.